Season effects on the composition of milk produced by a Holstein herd managed under semi-confinement followed by compost bedded dairy barn management - Weber, Carol Thaís; Schneider, Catia Letícia Corrêa; Busanello, Marcos; Calgaro, Júlia Laize Bandeira; Fioresi, Júnior; Gehrke, Cássio Rodrigo; Conceição, Jardel; Haygert-Velho, Ione Maria Pereira (Semina: Ciências Agrárias, 2020)
Here, we studied the composition of milk produced by a Holstein herd in the municipality of Nova Boa Vista, Rio Grande do Sul (RS), Brazil. The herd was first managed under a semi-confinement system and subsequently, in a compost bedded dairy barn system to facilitate animal management and, more importantly, family work. We monitored milk production by the herd under a semi-confinement system from January 2013 through September 2015, and then under a compost bedded dairy barn system from October 2015 through December 2017. The seasons of the year were spring (October to December), summer (January to March), autumn (April to June), and winter (July to September). Our results showed an increase in somatic cell count and total bacterial count with the change from semi-confinement to the compost bedded dairy barn system, possibly due to management factors; however, no changes were observed for any other of the variables under study, including lactose, fat, protein, and total solids. In addition, season markedly influenced milk composition and quality; thus, in winter and spring, milk was of a higher quality, whereas in the hotter months of summer and autumn fodder quality and availability, and the incidence of mastitis, as reflected by somatic cell count, affected milk quality negatively.